2017
DOI: 10.1186/s40168-017-0265-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inhaled aztreonam on the cystic fibrosis lung microbiome

Abstract: BackgroundAztreonam lysine for inhalation (AZLI) is an inhaled antibiotic used to treat chronic Pseudomonas aeruginosa infection in CF. AZLI improves lung function and quality of life, and reduces exacerbations-improvements attributed to its antipseudomonal activity. Given the extremely high aztreonam concentrations achieved in the lower airways by nebulization, we speculate this may extend its spectrum of activity to other organisms. As such, we sought to determine if AZLI affects the CF lung microbiome and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 51 publications
7
62
0
Order By: Relevance
“…In some studies, PEx onset was associated with transient changes in abundance of a number of taxa, such as anaerobes [34] and Gemella [35]. However, studies have also shown that sputum microbiota within patients exhibited remarkable resilience, returning to their baseline states after treatment ceased [27,28,32,33,36,37]. Interestingly, there is little evidence that the density of canonical CF pathogen Pseudomonas aeruginosa changes appreciably during exacerbation [38], and the degree to which antibiotics reduce P. aeruginosa levels following treatment has not been correlated with therapeutic success [39].…”
Section: Antimicrobial Treatment and Exacerbation Eventsmentioning
confidence: 99%
“…In some studies, PEx onset was associated with transient changes in abundance of a number of taxa, such as anaerobes [34] and Gemella [35]. However, studies have also shown that sputum microbiota within patients exhibited remarkable resilience, returning to their baseline states after treatment ceased [27,28,32,33,36,37]. Interestingly, there is little evidence that the density of canonical CF pathogen Pseudomonas aeruginosa changes appreciably during exacerbation [38], and the degree to which antibiotics reduce P. aeruginosa levels following treatment has not been correlated with therapeutic success [39].…”
Section: Antimicrobial Treatment and Exacerbation Eventsmentioning
confidence: 99%
“…Overall, there is certainly evidence that acute antibiotic administration alters the respiratory microbiota; however, in the absence of prospective controlled trials, it is difficult to interpret these results given the confounders mentioned above. Indeed there have been calls for future clinical trials in CF to include biobanking of samples to allow a more rigorous scrutiny of the effect of antibiotic agents on the microbiome [54].…”
Section: Community Changes Associated With Treatment For Acute Pulmonmentioning
confidence: 99%
“…Perhaps intrigued by the failure of AZLI to be associated with microbiomic differences given its proven clinical benefits, the same group investigated its effects in more detail. In the only published study focussing on the microbiomic outcomes of a specific inhaled antibiotic, Heirali et al [54] utilised the same Canadian biobank and sequenced 80 samples from 24 patients naive to AZLI and 82 samples from the same patients following initiation of AZLI. Overall no differences were observed in alpha or beta diversity measures, but at the OTU level, significantly lower relative abundances of Prevotella were seen following AZLI initiation.…”
Section: Community Changes Associated With Chronic Suppressive Antibimentioning
confidence: 99%
“…For example, recent changes in CF clinical care are likely to have contributed, directly and indirectly, to the increasing prevalence of Burkholderia multivorans , Stenotrophomonas maltophilia , Alcaligenes ( Achromobacter ) xylosoxidans , methicillin-resistant Staphylococcus aureus , P. aeruginosa (including multidrug-resistant P. aeruginosa ), and Mycobacterium abscessus complex in the CF population [3741]. Recent studies have described the impact of specific therapies on the CF lung microbiome, such as inhaled aztreonam [42], and such approaches are likely to prove particularly valuable in understanding the impact of the widespread deployment of CFTR modifiers and potentiators. This new generation of therapies could fundamentally alter the characteristics of airway disease for many individuals with CF, and while their influence on lung microbiology is still unclear, a recent study of ivacaftor treatment has reported a rapid and substantial reduction in sputum bacterial abundance, with a particularly marked effect on P. aeruginosa levels [43].…”
Section: Tracking Changes In Cf Airway Microbiologymentioning
confidence: 99%